Risk and uncertainty in projects management: literature review and conceptual framework - do Vale, Joao Walter Saunders Pacheco; Carvalho, Marly Monteiro de (Revista Gestão da Produção Operações e Sistemas, 2017)
This article analyzes the relationship between risk and uncertainty in Project Management.  The methodological approach selected is a systematic literature review, merging bibliometrics, network analysis and content analysis. The results present the most cited authors, keywords networks, research trends and gaps. Both definitions, risks and uncertainties, were analyzed. It could be verified that most publications use the terms as synonym.  This study described the conceptual model that could help research and organizations to understand the main construct and variables related to integrated management systems.